Salt-Templated Synthesis of 2D Metallic MoN and Other Nitrides - Xiao, Xu; Yu, Huimin; Jin, Huanyu; Wu, Menghao; Fang, Yunsheng; Sun, Jiyu; Hu, Zhimi; Li, Tianqi; Wu, Jiabin; Huang, Liang; Gogotsi, Yury; Zhou, Jun (ACS nano, 2017)
Two-dimensional (2D) transition-metal nitrides just recently entered the research arena, but already offer a potential for high-rate energy storage, which is needed for portable/wearable electronics and many other applications. However, a lack of efficient and high-yield synthesis methods for 2D metal nitrides has been a major bottleneck for the manufacturing of those potentially very important materials, and only MoN, Ti4N3, and GaN have been reported so far. Here we report a scalable method that uses reduction of 2D hexagonal oxides in ammonia to produce 2D nitrides, such as MoN. MoN nanosheets with subnanometer thickness have been studied in depth. Both theoretical calculation and experiments demonstrate the metallic nature of 2D MoN. The hydrophilic restacked 2D MoN film exhibits a very high volumetric capacitance of 928 F cm–3 in sulfuric acid electrolyte with an excellent rate performance. We expect that the synthesis of metallic 2D MoN and two other nitrides (W2N and V2N) demonstrated here will provide an efficient way to expand the family of 2D materials and add many members with attractive properties.